The location of meaning in the postmodernist literary text: a reading of Mark Z. Danielewski's House of Leaves and related material - Jeffery, Thomas Carnegie (Rhodes University, Faculty of Humanities, Department of Literary Studies in English, 2004)
In House of Leaves, Mark Z. Danielewski has produced a text which epitomises the traits and concerns of postmodernist literature. Through his attention to aspects such as metafiction, intertextuality and parody, Danielewski develops a narrative structure which is best understood as a literary labyrinth. It is a structure intended to reflect the social conditions of the twenty-first century and comment on the experience of people living at this time. Some of the meaning-making strategies within the book's labyrinthine structure are thus discussed in detail in order to demonstrate the relevance and importance of House of Leaves as social commentary. House of Leaves is an exemplary postmodernist text, but it is also one that seeks to guide the reader beyond the intellectual impasse of the postmodernist paradigm toward a renewed ethical and political engagement with the world. One of the most important goals of both Danielewski's novel and this thesis is to attempt to redefine the postmodernist perspective in such a way as to insist on the necessity of what I call a new realism. This is founded upon an awareness of the pervasiveness of the self-perpetuating ideology of capitalism, even in the perspective of postmodernism (which purports to subvert all authoritative ideologies). Playing a crucial role in perpetuating the status quo of capitalism is the growth of entertainment culture, which works to sideline crucial political issues by replacing information with infotainment. The result is an intensification of the processes of commodification. Such an intensification, it is argued, may be countered by a radical scepticism which draws upon the methods and insights of contemporary science.
Keywords: Danielewski, Mark Z. House of leaves; Danielewski, Mark Z. Criticism and interpretation; Horror tales; English literature -- Criticism, Textual; Literature, Modern -- History and criticism; Postmodernism (Literature)